2022
DOI: 10.1021/jacs.2c10669
|View full text |Cite
|
Sign up to set email alerts
|

Developing Waste Forms for Transuranic Elements: Quaternary Neptunium Fluorides of the Type NaxMNp6F30 (M = Ti, V, Cr, Mn, Fe, Co, Ni, Al, Ga)

Abstract: A series of quaternary Np(IV) fluorides was synthesized using a mild hydrothermal synthesis approach. The compositions are all of the type Na x MNp6F30, where M = Ti(III), V(III), Cr(III), Mn(II), Fe(III), Co(II), Ni(II), Al(III), and Ga(III) and x = 4 for divalent metals, x = 3 for trivalent metals. The compounds all crystallize in the P-3c1 space group and are isotypic with actinide analogues Na x MAn6F30 (An = Ce, U, Th, Pu). Structure data from the neptunium crystals were combined with data from the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…For later actinides particularly, issues both of supply and high radioactivity limit the amount of material available, complicating synthesis. For such species, hydrothermal synthesis has been shown to be scalable down to very small sample reaction masses, [25,[204][205][206] using as little as <1 mg of actinide [206]. Recently, we have shown that flux growth can also be scaled down to the mg scale or even 1 mg scale [207,208].…”
Section: Crystal Growthmentioning
confidence: 99%
“…For later actinides particularly, issues both of supply and high radioactivity limit the amount of material available, complicating synthesis. For such species, hydrothermal synthesis has been shown to be scalable down to very small sample reaction masses, [25,[204][205][206] using as little as <1 mg of actinide [206]. Recently, we have shown that flux growth can also be scaled down to the mg scale or even 1 mg scale [207,208].…”
Section: Crystal Growthmentioning
confidence: 99%
“…For the hydrothermal route using aqueous HF, we established that mild conditions, 160–200 °C and relatively short reaction times, 24 h, followed by slow cooling to room temperature, often yielded high-quality crystals of ternary and quaternary fluorides whose structures could readily be determined. We have used this approach to explore, in general, the preparation of transition metal- and rare earth-containing fluorides and oxyfluorides, including vanadates, niobates, tantalates, tungstates, molybdates, manganates, cobaltates, nickelates, and cerates, as well as numerous actinide-containing fluoride phases containing Th, U, Np, Pu, and Am. ,, , During this process, by experience, we have learned much about how to choose the optimum reaction conditions. In recent work, we explored hafnium fluorides, which yielded a number of hydrated phases, including Cs 2 [M­(H 2 O) 6 ]­[Hf 2 F 12 ] (M = Ni, Co, and Zn) and CuHfF 6 (H 2 O) 4 .…”
Section: Introductionmentioning
confidence: 99%